2006
DOI: 10.1136/hrt.2006.079707
|View full text |Cite
|
Sign up to set email alerts
|

Effects of serial levosimendan infusions on left ventricular performance and plasma biomarkers of myocardial injury and neurohormonal and immune activation in patients with advanced heart failure

Abstract: Serial levosimendan treatments improved left ventricular performance and modulated neurohormonal and immune activation beneficially in patients with advanced heart failure, without increasing myocardial injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
38
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(44 citation statements)
references
References 20 publications
5
38
0
1
Order By: Relevance
“…Serial infusions of LEVO in patients with the same characteristics and with a similar protocol has reached encouraging results also in other Heart Failure centers. 16,17 These preliminary data seem to be corroborated by a recent meta-analysis. 29 Although the number of patients with advanced heart failure is increasing, their treatment is often unsatisfactory because new pharmacological options are missing.…”
Section: Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…Serial infusions of LEVO in patients with the same characteristics and with a similar protocol has reached encouraging results also in other Heart Failure centers. 16,17 These preliminary data seem to be corroborated by a recent meta-analysis. 29 Although the number of patients with advanced heart failure is increasing, their treatment is often unsatisfactory because new pharmacological options are missing.…”
Section: Discussionsupporting
confidence: 62%
“…3,4 In accordance with other experiences on the use of LEVO in patients with unstable but not acute heart failure, our data confirm that, due to its inodilator properties, the drug acutely affects the hemodynamic status, 10 improves left ventricular systolic and diastolic function, 15 reduces the severity of functional mitral regurgitation, 26 and improves neurohormonal balance. 16 Moreover, serial LEVO infusions seemed to induce a favorable reverse remodelling, accompanied by a durable reduction in BNP levels. These results may be partially explained by the persistent effects of the active metabolite OR-1896, 27 in itself a calcium sensitizer; however, it is tempting to speculate that they can derive from a sustained hemodynamic change interrupting a vicious circle because they lasted more than the previously described effects of a single LEVO infusion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Plasma levels of the levosimendan active metabolite OR‐1896 had declined to very low levels by the end of the 14‐day intertreatment intervals, which suggests that either a higher total dose of levosimendan or shorter dosing interval might be advantageous. Beneficial effects of serial levosimendan treatment have been reported in patients with advanced heart failure 27 …”
Section: Discussionmentioning
confidence: 99%
“…[11][12][13][14] However, development of more sophisticated imaging techniques enables further evaluation of myocardial contractility and relaxation and, hence, further evaluation of the drug effects on myocardial function. 19 In addition, it has been shown that the maximal hemodynamic response to levosimendan is seen for 24-48 hours after stopping the infusion. Strain and strain rate measurements can demonstrate deterioration of myocardial tissue before a reduction in the EF appears.…”
Section: Introductionmentioning
confidence: 99%